Effectiveness of Aspirin Dose in Preventing Preeclampsia in High-Risk Group: A Meta-Analysis - Simanjuntak, Tigor Peniel; Elena, Elena; Sirait, Batara Imanuel (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Preeclampsia is hypertension that occurs after 20 weeks of pregnancy and is accompanied by impaired function of the mother’s organs or the uteroplacental unit. Purpose: To evaluate the efficacy of aspirin doses in preventing preeclampsia in high-risk populations. Method: This study follows the PRISMA protocol. The reviewers examined all the findings and selected studies that met the inclusion criteria and PICO analysis. Statistical analysis was performed using Review Manager 5.4 software. A total of 14 journals met the inclusion criteria with searches in four databases (PubMed, Science Direct, Google Scholar, and Plos One). Result: Aspirin significantly reduced the incidence of preeclampsia in the high-risk group (RR 0.83 [95% CI: 0.78, 0.88], P<0.00001), reducing the incidence of preeclampsia by 50 mg/day (RR 0.56 [95% CI: 0.36, 0.86] P=0.008), 60 mg/day (RR 0.87 [95% CI: 0.81, 0.93] P <0.0001), 75 mg/day (RR 0.54 [95% CI: 0.40, 0.73] P<0.0001), 80-81 mg/day (RR 0.72 [95% CI: 0.56, 0.94] P=0.02), and 150 mg/day, reduced the incidence of PE (P<0.00001). Conclusion: The results of the study show that the best dose of aspirin to prevent PE in high-risk groups is 75 mg/day.Efektivitas Dosis Aspirin untuk Mencegah Preeklamsia pada Kelompok Risiko Tinggi: Sebuah MetaanalisisAbstrakPendahuluan: Preeklamsia adalah hipertensi yang terjadi setelah usia kehamilan 20 minggu dan disertai dengan gangguan fungsi organ ibu atau uteroplasenta. Tujuan: Untuk mengetahui efektivitas dosis aspirin untuk mencegah preeklamsia pada kelompok risiko tinggi. Metode: Penelitian ini mengikuti protokol PRISMA. Para peninjau memeriksa semua temuan dan memilih penelitian yang memenuhi kriteria inklusi dan analisis PICO. Analisis statistik dilakukan dengan menggunakan perangkat lunak Review Manager 5.4. Terdapat 14 jurnal yang memenuhi kriteria inklusi dengan pencarian di 4 database (PubMed, Science Direct, Google Scholar, dan Plos One). Hasil: Aspirin secara signifikan menurunkan kejadian preeklampsia pada kelompok risiko tinggi (RR 0,83 [95% CI: 0,78, 0,88], P<0,00001), menurunkan kejadian preeklamsia sebesar 50 mg/hari (RR 0.56 [95% CI: 0.36, 0.86] P=0.008), 60 mg/hari (RR 0.87 [95% CI: 0,81, 0.93] P <0,0001), 75 mg/hari (RR 0,54 [95% CI: 0,40, 0,73] P<0,0001), 80-81 mg/hari (RR 0,72 [95% CI: 0,56, 0,94] P=0,02), dan 150 mg/hari, mengurangi kejadian PE (P<0,00001). Kesimpulan: Hasil penelitian menunjukan bahwa dosis aspirin terbaik untuk mencegah PE pada kelompok risiko tinggi adalah 75 mg/hari.